In vitro enzymatic stabilities of methionine-enkephalin analogues containing an adamantane-type amino acid - Roščić, Maja, inženjerka kemije (Array, 2008)
Abstract: The enzymatic stability of synthetic methionine-enkephalin peptide analogues containing an unnatural amino acid of the adamantane-type 3-5 was examined in human serum, at 37 °C, and compared with the results of the degradation of the parent endogenous pentapeptide 1 and the tripeptide, Tyr-Gly-Gly (2). Methionine-enkephalin (Tyr-Gly-Gly-Phe-Met, 1) and tripeptide 2 are rapidly degraded in 80 % human serum with half-lives of 12.2 and 23.0 minutes, respectively, preferably by aminopeptidase cleavage of the N-terminal Tyr-Gly peptide bond. Incorporation of the rigid and sterically hindered 1-adamantylglycine moiety into the peptide sequence resulted in increased stability of compound 3, while compounds 4a and 5a were not at all susceptible to the enzymes present in human serum. Strong binding of peptides 3-5 to human serum proteins was demonstrated